2019
DOI: 10.1002/biof.1503
|View full text |Cite
|
Sign up to set email alerts
|

Hydroalcoholic extract from Baccharis dracunculifolia recovers the gastric ulcerated tissue, and p‐coumaric acid is a pivotal bioactive compound to this action

Abstract: Baccharis dracunculifolia is a medicinal plant native to southeastern Brazil and is the main botanical source used by bees (Apis mellifera) in the manufacture of green propolis and display similar gastroprotective action and chemical profile. This article reports the healing gastric ulcer activity of the hydroethanolic extract of B. dracunculifolia (HEBD) in an acetic acid-induced ulcer model. In addition to the extract, the isolated compounds ferulic acid, p-coumaric acid, caffeic acid, baccharin, and aromade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
2
15
0
1
Order By: Relevance
“…Automatic gain control was set at 3E6 loads and 250 ms maximum injection time, 70,000 resolutions, and a scan time of 2.5 scans/s. The content of coumaric acid in HEBD was previously verified and was 5% in the dry extract, as Costa et al [ 14 ] described.…”
Section: Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…Automatic gain control was set at 3E6 loads and 250 ms maximum injection time, 70,000 resolutions, and a scan time of 2.5 scans/s. The content of coumaric acid in HEBD was previously verified and was 5% in the dry extract, as Costa et al [ 14 ] described.…”
Section: Methodsmentioning
confidence: 78%
“…Luceri et al [ 37 ] described that the p-coumaric acid at 50 mg/kg attenuated the intestinal inflammation induced by DSS due to its ability to suppress COX-2 expression and activity. Moreover, our research group showed the gastric healing effects of p-coumaric acid at a 15 mg/kg dose in rats [ 14 ]. Therefore, it is possible to infer that the p-coumaric acid may participate in the intestinal anti-inflammatory effects of the extract along with other constituents and not as an isolated mediator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sendo seu cultivo considerado viável e com interessante potencial comercial (GONÇALVES, et al, 2005;GOBBO-NETO;LOPES, 2007;DE SOUSA, et al, 2011;SIMIONI, et al, 2013). Diferentes estudos demostraram a atividade biológica desses metabólicos frente a experimentos de citotoxicidade contra células tumorais, ensaios antivirais, diabetes, ações imunomoduladoras, atividade antioxidante, analgesia, atividade anti-inflamatória, ensaios antiúlceras e antimicrobianos (PEREIRA, 2014;FIGUEIREDO-RINHEL, et al, 2017;CAZELLA et al, 2019;COSTA, 2019. Os antibióticos podem ser compostos de origem natural ou sintéticos, compostos estes capazes de inibir o crescimento ou causar a morte dos microrganismos caracterizando-os como bactericidas ou bacteriostáticos. Depois da descoberta da penicilina e sua industrialização, nos anos de 1940 até 1960, foram descobertos diversas substâncias naturais com atividade antimicrobiana (CALIXTO, CAVALHEIRO, 2012).…”
Section: Introductionunclassified